Description of Factors Affecting The Completeness of Tetanus Toxoid Immunization in Trimester III Pregnant Women at Poskesdes Village Bumi Serdang Tungkal Ilir Districts Banyuasin Regency in 2021 - Ratna Dewi (Institute of Computer Science (IOCS), 2021)
Tetanus neonatorum and maternal tetanus can increase maternal mortality and infant mortality rates. One of the prevention of tetanus is to immunize pregnant women with tetanus toxoid. Pregnant women who do not do TT immunization because they have several factors that affect the completeness of tetanus toxoid immunization, namely age, education, occupation, parity and maternal knowledge which can have an impact on increasing the incidence of neonatal tetanus. This study aims to describe the factors that influence the completeness of tetenuas toxoid immunization in third trimester pregnant women. This research method is descriptive quantitative using cross sectional. The population in this study were all third trimester pregnant women in Poskesdes Desa Bumi Serdang, Tungkal Ilir Subdistrict, Banyuasin Regency in 2021. The sample consisted of 11 respondents using nonprobability sampling technique, namely the total population. The results showed that the factors that influenced the completeness of tetanus toxoid immunization for pregnant women were age and knowledge of the mother. Of the 11 respondents, most of the mothers had mature age, namely 9 people (81.8%) and most of them had high knowledge, namely 8 people (72.7%). The more pregnant women have a mature age and have high knowledge, it will affect their behavior and attitudes in choosing and making the right choices in health services.